DESCRIPTION OF SELF-EFFICACY REGARDING MEDICATION ADHERENCE AMONG PEOPLE LIVING WITH HIV/AIDS IN KUPANG CITY, EAST NUSA TENGGARA - Wahyuni, Maria Magdalena Dwi Wahyuni; Landi, Soleman; Benu, Putra James; Neolaka, Jefri Arisamsi; Tukan, Maria Kurniawati; Mathilde, Mauricia Keyra; Gaa, Jesica Margareta; Sabuna, Putri Meldi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2026)
The role of self-efficacy in antiretroviral medication adherence is a critical factor in ensuring therapeutic success for people living with HIV/AIDS, particularly given the rising number of cases in Kupang City. This study describes self-efficacy related to treatment adherence using a qualitative descriptive approach. Data were collected through in-depth interviews and observations of five participants registered in HIV services. Informants were selected via purposive sampling, and the data were analyzed and presented descriptively to illustrate patterns of adherence and the factors influencing self-efficacy. The results indicate that all participants possess strong confidence in their daily medication routines, experience no significant side effects, and have achieved positive clinical outcomes. High self-efficacy is driven by internal motivation, family responsibilities, and emotional and instrumental support from their environment. Additionally, assistance from fellow survivors—who facilitate medication access and provide psychological reinforcement—plays a vital role. Together, these factors foster positive habits that sustain therapy compliance. This study concludes that robust self-efficacy, reinforced by social support, is the foundation for maintaining medication adherence. These findings emphasize the need for interventions focused on boosting self-efficacy, providing continuous education, and strengthening peer support groups to ensure long-term treatment success.